The Influence of Shopping Motives on Impulse Buying Through Shopping Lifestyle on Tokopedia in Indonesia - Sukma Irdiana; Budiyanto Budiyanto; Suhermin Suhermin (Maneggio, 2025)
This study aims to analyze the influence of shopping motives on impulse buying with shopping lifestyle as a mediating variable among Tokopedia users in Indonesia. This study uses a quantitative method with an explanatory research approach. The research sample is Tokopedia users who have made transactions at least twice in the last six months, with a total of 200 respondents selected through purposive sampling. The research instrument is an online questionnaire with a Likert scale, and the data are analyzed using Structural Equation Modeling (SEM-PLS). The results show that shopping motives have a positive and significant effect on impulse buying, shopping motives have a positive and significant effect on shopping lifestyle, and shopping lifestyle has a positive and significant effect on impulse buying. Shopping lifestyle is proven to partially mediate the relationship between shopping motives and impulse buying. This finding provides a theoretical contribution in strengthening the literature on consumer behavior in the digital era, as well as practical implications for Tokopedia in designing consumer lifestyle-based marketing strategies to increase impulse buying.